2018
DOI: 10.1186/s13620-018-0136-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of midazolam on cardiovascular responses and isoflurane requirement during elective ovariohysterectomy in dogs

Abstract: BackgroundA prospective, randomized, placebo-controlled, blinded clinical study was conducted to determine whether a single dose of midazolam affects the cardiovascular response to surgical manipulation of the ovaries during elective ovariohysterectomy. Thirty-nine client-owned dogs undergoing elective ovariohysterectomy were recruited. After scoring cage demeanour, dogs were premedicated with acepromazine (0.03 mg kg-1) and pethidine (3 mg kg-1) intramuscularly into the quadriceps muscle and 20 min later seda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 67 publications
(66 reference statements)
1
7
0
2
Order By: Relevance
“…Antiepileptic medications have not been shown to alter BP in dogs; however, they may sedate animals and blunt any situational hypertension. 27,28 However, in the 16 dogs that were stable on long-term medication, we believe this effect would have been decreased. Clinically, our experience is that these dogs are often more stressed in the ICU than the critical patients.…”
Section: Discussionmentioning
confidence: 90%
“…Antiepileptic medications have not been shown to alter BP in dogs; however, they may sedate animals and blunt any situational hypertension. 27,28 However, in the 16 dogs that were stable on long-term medication, we believe this effect would have been decreased. Clinically, our experience is that these dogs are often more stressed in the ICU than the critical patients.…”
Section: Discussionmentioning
confidence: 90%
“…In fact, in animals with low cardiac output or low blood pressure, the onset of action may be delayed due to the vasodilation caused by some pre-anaesthetic medications [ 3 ]. In this study, the pre-anaesthetic midazolam, causing minimal cardiovascular changes at clinically relevant doses [ 23 , 24 ], allowed us to avoid this inconvenience. Although some studies reported behavioural alterations in dogs after the administration of midazolam alone, due to its excitatory effects, such as an increased motor activity associated with an intense sniffing [ 25 , 26 ], in the present clinical study, no subject showed similar side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Midazolam sedasyonunun hastaların rölatif hipovolemisini artırdığını düşündük. [16][17][18][19][20][21][22][23]27 Biz, çalışmamızda, iki kez PBKT i uyguladık, birincisi midazolam uygulanması yapılmadan önceydi; supin pozisyon ve PBKT sonrası iki kez SAB, CI, CO, VTI ölçümü yaptık. Midazolam…”
Section: Discussionunclassified
“…16 PBKT, hipovolemiyi EKO parametreleriyle de tanımlayabilir. [17][18][19][20][21] PBKT yapmadan da VCI-CI, delta velocite peak (Delta Vpeak) ve kardiyak out-put (CO) artış yüzdesi ile de hipovolemi tanısı konabilir. 13,22,23 Sedatif ilaçlar, yoğun bakım ünitelerinde yatan hastalarda sık kullanılan ilaçlardır.…”
unclassified